2007
DOI: 10.1373/clinchem.2006.076885
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health Outcomes Associated with Detectable Troponin I Concentrations

Abstract: Background: Recent data suggest that older men with detectable cardiac troponin I (cTnI) concentrations that remain below the 99th percentile concentration cutoff are at increased risk for subsequent cardiovascular events. We designed this study to extend this observation by examining risk prediction in both men and women presenting to an emergency department with chest discomfort. Methods: We obtained data for all-cause mortality and hospital discharges associated with either acute myocardial infarction (AMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…The study population and its characteristics have been previously reported [2,7]. Briefly, after ethics approval in 1996, consecutive unique patients presenting to the emergency department with symptoms suggestive of ACS were recruited for a cardiac marker study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study population and its characteristics have been previously reported [2,7]. Briefly, after ethics approval in 1996, consecutive unique patients presenting to the emergency department with symptoms suggestive of ACS were recruited for a cardiac marker study.…”
Section: Methodsmentioning
confidence: 99%
“…After measurement by the cytokine array, the same EDTA plasma specimens were assayed for NT-proBNP with the Elecsys® 1010 Roche analyzer (interassay CV<7%). This patient cohort previously had cTnI measured (AccuTnI, Beckman Coulter) in heparin specimens in 2003 [7], and both NTproBNP and cTnI are stable during long-term storage [2,7]. As we had prior data suggesting that both NT-proBNP and cTnI add to the prognostic accuracy of risk prediction, we included these biomarkers in the hazard analysis models.…”
Section: Biomarker Measurementsmentioning
confidence: 99%
See 3 more Smart Citations